Antiarthritic potential of berberine loaded invasomal gel - Shweta Jain; Shalini Tripathi; Pushpendra Kumar Tripathi (Elsevier, 2022)
Background: Numerous plants and plant isolates have been widely reported for the treatment of arthritis. Berberine, a cationic flavonoid, obtained from Berberis aristata DC. (Berberidaceae) has been well reported for the treatment of arthritis. The lipid-based vesicular system including invasomes overcome the stratum corneum barrier and can effectively deliver drugs beneath the skin. Methods: The aim of the present study is to prepare berberine-loaded invasomes by the thin film hydration method. Prepared berberine-loaded invasomes were characterised for particle size and shape, zeta potential, entrapment efficiency, and skin permeation studies. These prepared berberine-loaded invasomes were further utilizesd for the preparation of gel containing carbomer for transdermal delivery. Prepared berberine-loaded invasomal gel was evaluated for homogeneity, viscosity, pH, speradability, extrudability, drug content, skin irritant and stability studies. Results: The in vivo analgesic activity of prepared berberine-loaded invasomal gel using the tail-flick hotwater immersion method, revealed potential analgesic activity for a prolonged period of time. Furthermore, the anti-arthritic activity of berberine-loaded invasomal gel was evaluated in CFA-induced arthritis rat model by measuring paw diameter, which showed a considerable reduction after treatment, as compared to standard gel (omnilgel, 0.1%). Topical application of berberine-loaded invasomal gel improves haematological factors and normalizes proinflammatory biomarkers. The radiographical analysis of hind paw rats in CFA model showed bone resorption, definite joint gap reduction, and considerable connective tissue expansion after treatment with prepared berberine-loaded invasomal gel. Histopathological examination of ankle joints also confirms the deeper penetration ability of invasomes through berberine-loaded invasomal gel and produces profound effects. Conclusion: The results revealed that the berberine-loaded invasomal gel has significant arthritic activity in the CFA rat model.